2022
DOI: 10.3390/brainsci12020137
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing Phenotypes in Phelan-McDermid Syndrome and SYNGAP1-Related Intellectual Disability

Abstract: Sensory processing differences are an established feature of both syndromic and non-syndromic Autism Spectrum Disorders (ASDs). Significant work has been carried out to characterize and classify specific sensory profiles in non-syndromic autism. However, it is not known if syndromic autism disorders, such as Phelan-McDermid Syndrome (PMD) or SYNGAP1-related Intellectual Disability (SYNGAP1-ID), have unique sensory phenotypes. Understanding the sensory features of these disorders is important for providing appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…In this case, 92% of the sample showed behaviors associated with hyporesponsive patterns and 65% with sensory seeking. Similar results were also identified in previous studies employing the SPP for the assessment of patients with PMS, with definite sensory differences in underresponsive/seek sensation [12,13,15]. Likewise, studies on PMS by Mieses et al [12] and Droogmans, Swillen, and Van Buggenhout [13] identified a high percentage of sensory responses associated with probable or definite differences in the low energy/ weak sensory category.…”
Section: Sensory Processingsupporting
confidence: 84%
See 4 more Smart Citations
“…In this case, 92% of the sample showed behaviors associated with hyporesponsive patterns and 65% with sensory seeking. Similar results were also identified in previous studies employing the SPP for the assessment of patients with PMS, with definite sensory differences in underresponsive/seek sensation [12,13,15]. Likewise, studies on PMS by Mieses et al [12] and Droogmans, Swillen, and Van Buggenhout [13] identified a high percentage of sensory responses associated with probable or definite differences in the low energy/ weak sensory category.…”
Section: Sensory Processingsupporting
confidence: 84%
“…In fact, hyporeactive profiles have generally been associated with limitations in the development of appropriate adaptive behaviors of interaction, communication, and social participation with adults and peers [17]. In contrast, although the low energy/weak variable was also consistent with a hyporeactivity profile in the SSP and all previous literature (12)(13)(14)(15) has highlighted significant differences in the sensory profile of the PMS in this category, our results indicate that it does not appear to significantly influence adaptive skills. Even so, in our study, the results obtained in the linear regression model identified a significant effect of the underresponsiveness/seek sensation and auditory filtering categories on the adaptive skills needed to participate in leisure activities or in environments such as home or school.…”
Section: Adaptive Functioningsupporting
confidence: 46%
See 3 more Smart Citations